BAITUL MAL IN SAMBAS IN THE COLONIAL PERIOD: The History of Establishment And Management - Sunandar, Sunandar; Posha, Beti Yanuri; Lamazi, Lamazi; Yusnita, Henny (Jurisdictie: Jurnal Hukum dan Syariah, 2021)
Baitul Mal management in the Sultanate of Sambas started from the establishment of Ulamaâ€™s official institution, so the state could supervise the religious issues. Through the Maharaja Imam, Muslim affairs were handled. The permanent management improvement of Baitul Mal in the Sultanate of Sambas was started in 1944, through Ulamaâ€™s discussion in the Sambas Kingdom consisting of Imam, Khatib, and Penghulu. They formulated 37 articles concerning the cost of marriage, divorce, reconciliation, alms (zakat mÄl, and zakat fitrah), procedures for withdrawal, distribution, and the eligible recipients of funds. The Baitul Mal founding was interfered by a fundamental problem, caused by political issues within Sambas society. Those issues included Japanâ€™s defeat in 1945, the NICA arrival followed by the Dutch expulsion in 1949, and the PGRS-PARAKU incidents until 1965. Since the early days, Baitul Mal management in Sambas has found its form and can move social life through the funds distribution, one of which is to support the schools in Sambas. Baitul Mal in Sambas is currently in crisis due to the existence of new zakat institutions both semi-government and private such as Badan Amil Zakat (BAZ). Therefore, they really need to have the people-oriented management.Pengelolaan Baitul Mal di wilayah Kesultanan Sambas dimulai dari pembentukan lembaga resmi ulama, sehingga pengurusan masalah keagamaan ditangani oleh negara. Melalui Maharaja Imam, urusan Muslim ditangani. Perbaikan pengelolaan Baitul Mal secara permanen di Kesultanan Sambas dimulai pada tahun 1944, melalui musyawarah yang dihadiri oleh para ulama di Kerajaan Sambas yang terdiri dari Imam, Khatib dan Penghulu. Dalam rapat tersebut dirumuskan 37Â pasal tentang masalah biaya perkawinan, perceraian, rukun, sedekah (zakat mal dan zakat fitrah), tata cara penarikan, penyaluran /distribusi dana dan orang-orang yang berhak menerimanya. Pembentukan Baitul Mal mengalami masalah yang mendasar, yang diakibatkan oleh masalah politik yang dihadapi oleh masyarakat Sambas, mulai dari kekalahan Jepang kepada Sekutu pada tahun 1945, yang diikuti kedatangan NICA hingga pengusiran Belanda pada tahun 1949, peristiwa PGRS-PARAKU hingga tahun 1965. Manajemen Baitul Mal di Sambas sejak masa awal telah menemukan bentuknya dan mampu menggerakkan kehidupan sosial melalui distribusi dananya, salah satunya adalah menopang sekolah/madrasah yang terdapat di Sambas. Dalam carut marut pengelolaan Baitul Mal di Sambas saat ini yang ditandai dengan munculnya beragam lembaga dengan label Badan Amil Zakat (BAZ), semi pemerintah maupun swasta maka sangat dibutuhkan pengelolaan yang beorientasi pada kepentingan umat.